Preferred Valuation Techniques in the UAE: A Comparative Study of Financial and Nonfinancial Sectors - Aljifri, Khaled; Ahmad, Hafiz Imtiaz (International Journal of Economics and Financial Issues, 2019)
This study examines empirically the preferred valuation techniques used by UAE investment analysts in the financial and non-financial sectors. The study uses a questionnaire and interviews to address its ten research questions. Descriptive and nonparametric statistics were employed in this study. The results reveal that discounted cash flow and price earnings are the most preferred valuation techniques used by the analysts in the financial sector. On the other hand, the results show that the analysts in the non-financial sector prefer using EV/EBITDA and discounted cash flow techniques. The study concludes that the analysts in the two sectors use both sophisticated valuation techniques and unsophisticated valuations techniques, with a preference for cash flow techniques in the financial sector and a preference for accrual-based techniques in the non-financial sector. Keywords: Financial Analysts; Valuation Techniques; Cash Flow Techniques JEL Classifications: E22, G2 DOI: https://doi.org/10.32479/ijefi.7137